Hubungan Tingkat Pengetahuan Mahasiswa Profesi terhadap Kepatuhan Mencuci Tangan di RSGM IIK Bhakti Wiyata - Ramadhani Kusumastuti, Anisa; Khafid, Mohammad; Prastyo, Eko; Praptiwi, Armi Dita (Bhakta Dental Journal, 2023)
Infectious diseases are still the main cause of high morbidity and mortality rates in hospitals. Infections that occur in health services are called Health-care Associated Infections (HAIs) or nosocomial infections. As health workers, students of the dental profession have an obligation to control infection, by washing their hands according to WHO standards, because the hands are the dominant means of movement used when working so compliance with hand washing is very influential in preventing the chain of infection. This study aims to determine the relationship between the level of knowledge of dental professional students and hand washing compliance at RSGM IIK Bhakti Wiyata. This type of research is observational analytic with a cross-sectional design. The sampling technique used was simple random sampling with 100 respondents and processed using the SPSS Chi-Square test. The research results showed that the p value was 0.000 < 0.05, meaning there was a significant relationship. There is a relationship between the level of knowledge of dental professional students and their hand washing compliance at RSGM IIK Bhakti Wiyata.